Bahasa Melayu dan konsep kebenaran ilmu berdasarkan pandangan Syed Muhammad Naquib al-Attas - Musa, Hashim; Che Rodi, Rozita; Pondo, Halimah; Noor Muhammad, Salmah Jan (Penerbit Universiti Sains Malaysia, 2013)
The Malay language has been a medium of Islamic discourse for several hundred years, functioning among others, as the language of translation and interpretation of the Qur'an and Hadith, as well as the language of Islamic epistemology, ontology and legal edicts. However, the colonisation of the Malay world by western powers has been responsible in secularising the Malay mind and language. As a result, secular knowledge is now given importance whilst Islamic revealed knowledge is considered as religious knowledge only. This article begins with a discussion on the Islamisation of the Malays and Malay language based on Syed Muhammad Naquib al-Attas' theory which underlines two elements (1) the infusion of the elements of rational and sound reasoning, and (2) the transformation of the Malay language into an Islamic language, enriched with Islamic vocabulary, which functions as a discourse on Islamic knowledge in various literary genres. The article argues that, from the Islamic perspective, western secular knowledge has caused confusion in defining facts, data, knowledge and others in the Malay language.